Pelatihan Peningkatan Kompetensi Tutor Kesetaraan pada PKBM Panrita Kota Parepare - Nanda Oktavia Ramadhana; A Hasdiansyah; Ihwan Ridwan; Andi Jusman Tharihkh; Salmia Salama (Prodi PGSD Unsultra, 2026)
This community service program aimed to improve the competencies of equivalency education tutors at PKBM Panrita, Parepare City, through training and mentoring based on andragogical principles. The partner's main challenges included limited understanding of adult learners' characteristics, participatory learning strategies, the use of instructional media, feedback techniques, and reflective teaching practices. The program employed a participatory approach consisting of needs assessment, training, teaching simulations, mentoring, and reflective evaluation. The results demonstrated improved tutor competencies in applying adult learning principles, facilitating classroom discussions, utilizing contextual learning media, and designing assessment and follow-up learning plans. In addition, the program produced a competency needs map for tutors, a framework for tutor reflection forums, and recommendations for developing a repository of simple instructional media to enhance learning quality at PKBM. These findings indicate that needs-based training and mentoring effectively strengthen tutors' capacity to implement more participatory, contextual, and learner-centered instruction in equivalency education.